Platinum-doped iron-aluminum alloy magnetostrictive material and preparation method thereof
By doping Pt in the Fe-Al alloy, controlling the growth of grains in the <100> direction, the problem of low magnetostrictive performance of Fe-Al alloy is solved, and a significant increase in magnetostrictive value and cost reduction are achieved.
Patent Information
- Application Number
- CN202411622373.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-18
AI Technical Summary
The saturated magnetostrictive coefficient of Fe-Al alloy is low, which is difficult to meet market demand. At the same time, the selection of doped elements depends on trial and error methods, resulting in an increase in costs.
By doping Pt instead of Fe or Al, the growth of grains in the <100> direction is controlled to improve the magnetostrictive performance of magnetostrictive materials.
The magnetostrictive performance of magnetostrictive materials has been significantly improved, and the magnetostrictive value has been increased from 29 ppm to 50~80 ppm, and the cost has been reduced by precisely controlling the crystal growth direction.
Smart Images

Figure CN119464951A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of iron-aluminum-based magnetostrictive materials and relates to a platinum-doped iron-aluminum alloy magnetostrictive material and a preparation method thereof. Background Art
[0002] Magnetostriction refers to the physical phenomenon that the shape and size of ferromagnets or ferrimagnets change under the influence of an external magnetic field. Giant magnetostrictive materials are widely used in aviation, navigation, robotics, new energy, biomedicine and other fields due to their large magnetostriction coefficient, fast mechanical response and high energy density. Fe-Al alloy is a new type of giant magnetostrictive material studied in recent years after Tb-Dy-Fe alloy.
[0003] Compared with Tb-Dy-Fe alloy, binary Fe-Al alloy has the advantages of higher magnetostriction value, low cost, low brittleness, high strength, high magnetic permeability, high Curie temperature and excellent machinability, and is expected to replace Tb-Dy-Fe giant magnetostrictive material. However, the saturation magnetostriction coefficient of Fe-Al alloy is only 1 / 8 of that of Tb-Dy-Fe material, so improving its magnetostriction performance to meet market demand is the key at present; secondly, there is still a large gap between the magnetostriction value of Fe-Al alloy and market demand; other studies have shown that doping elements Tb or B is beneficial to the improvement of magnetostriction, but the reason behind it is that <100> The mechanism of texture enhancement is still unclear and relies more on trial and error, which leads to an increase in the cost of exploring effective doping elements.
[0004] Therefore, there is an urgent need to provide a method for predicting element doping and improving the magnetostrictive properties of iron-aluminum alloys through element doping. Summary of the invention
[0005] In order to overcome the above problems, the present invention provides a platinum-doped iron-aluminum alloy magnetostrictive material and a preparation method thereof. 0.80 Al 0.20 Alloy is used as the matrix, and Pt is doped to replace Fe or Al to control the grain <100> The magnetostrictive properties of the magnetostrictive material are improved by growing in the magnetostrictive direction, thereby completing the present invention.
[0006] Specifically, the purpose of the present invention is to provide the following aspects: On the one hand, a platinum-doped iron-aluminum alloy magnetostrictive material is provided, wherein the magnetostrictive material is Fe 0.80 Al 0.20 The alloy is the matrix and is obtained by doping Pt to replace Fe or Al.
[0007] Among them, by doping Pt instead of Fe or Al, the grain <100> direction to improve the magnetostrictive performance of the magnetostrictive material.
[0008] Wherein, in the magnetostrictive material, the energy of the crystal plane (100) is lower than that of the crystal plane (110).
[0009] Wherein, the magnetostrictive performance of the magnetostrictive material is 50~80 ppm.
[0010] Wherein, the magnetostrictive material has the following expression: (Fe 0.80 Al 0.20 ) 100-x Pt x , x In atomic percentage, 0.2 ≤ x ≤1.0.
[0011] On the other hand, a method for preparing the magnetostrictive material according to the first aspect is provided, the method comprising: Step 1, smelting raw materials to obtain magnetostrictive ingots; Step 2: homogenizing the magnetostrictive ingot to obtain the magnetostrictive material.
[0012] In step 1, the raw materials include iron, aluminum and platinum.
[0013] Wherein, the purity of the iron is not less than 99.9%.
[0014] Wherein, the purity of the aluminum is not less than 99.95%.
[0015] Wherein, the purity of the platinum is not less than 99.95% The beneficial effects of the present invention include: (1) The magnetostrictive material provided by the present invention is Fe 0.80 Al 0.20 Alloy is used as the matrix, and Pt is doped to replace Fe or Al to control the grain <100> direction, thereby improving the magnetostrictive properties of the magnetostrictive material.
[0016] (2) The magnetostrictive material method provided by the present invention effectively predicts the effect of platinum doping on the growth direction of Fe-Al alloy crystals, thereby accurately controlling the crystal growth direction, thereby improving the magnetostrictive performance of the Fe-Al alloy magnetostrictive material.
[0017] (3) The method for producing magnetostrictive materials provided by the present invention realizes precise control of the amount of platinum doping through arc melting technology, thereby further improving the performance of the material, and has high practical value and broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] By reading the detailed description of the preferred specific embodiments below, various other advantages and benefits of the present invention will become clear to those of ordinary skill in the art. The drawings in the specification are only used for the purpose of illustrating the preferred embodiments and are not considered to be limitations of the present invention. Obviously, the drawings described below are only some embodiments of the present invention. For those of ordinary skill in the art, other drawings can also be obtained based on these drawings without creative work.
[0019] In the attached picture: Figure 1 (a) shows a schematic diagram of a six-atom-layer slab model of the (100) crystal plane in Comparative Example 1; Figure 1 (b) shows a schematic diagram of a six-atom-layer slab model of the (110) crystal plane in Comparative Example 1; Figure 1 (c) shows a schematic diagram of a six-atom-layer slab model after the (100) crystal plane is doped with Pt in Example 2; Figure 1 (d) shows a schematic diagram of a six-atom-layer slab model after the (110) crystal plane is doped with Pt in Example 2; Figure 2 The XRD characterization of the crescent flakes obtained by melting in Examples 2-4 and Comparative Example 1 is shown; Figure 3 A comparison diagram of the peak normalized relative intensities of the magnetostrictive materials (100) prepared in Examples 2-4 and Comparative Example 1 is shown; Figure 4 The strain test diagrams of the crescent pieces obtained by melting in Examples 2-4 and Comparative Example 1 are shown; Figure 5 (a) shows the magnetic domain diagram of the magnetostrictive material prepared in Comparative Example 1; Figure 5 (b) shows the magnetic domain diagram of the magnetostrictive material prepared in Example 3; Figure 5 (c) shows the magnetic domain diagram of the magnetostrictive material prepared in Example 2; Figure 5 (d) shows the magnetic domain map of the magnetostrictive material prepared in Example 4. DETAILED DESCRIPTION
[0020] The following will refer to the attached Figures 1 to 5 Specific embodiments of the present invention are described in more detail. Although specific embodiments of the present invention are shown in the accompanying drawings, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to enable a more thorough understanding of the present invention and to fully convey the scope of the present invention to those skilled in the art.
[0021] The following will refer to the attached Figures 1 to 5 Specific embodiments of the present invention are described in detail. Although specific embodiments of the present invention are shown in the accompanying drawings, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to enable a more thorough understanding of the present invention and to fully convey the scope of the present invention to those skilled in the art.
[0022] It should be noted that certain words are used in the specification and claims to refer to specific components. Those skilled in the art should understand that technicians may use different nouns to refer to the same component. This specification and claims do not use the difference in nouns as a way to distinguish components, but use the difference in the functions of the components as the criterion for distinction. As mentioned throughout the specification and claims, "including" or "comprising" is an open term, so it should be interpreted as "including but not limited to". The subsequent description of the specification is a preferred embodiment of the present invention, but the description is based on the general principles of the specification and is not intended to limit the scope of the present invention. The scope of protection of the present invention shall be determined by the attached claims.
[0023] In the description of the present invention, it should be noted that the terms "upper", "lower", "inner", "outer", "front", "rear", etc. indicate positions or positional relationships based on the working state of the present invention, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", "third", and "fourth" are only used for descriptive purposes and cannot be understood as indicating or implying relative importance.
[0024] To facilitate understanding of the embodiments of the present invention, further explanation will be given below by taking specific embodiments as examples in conjunction with the accompanying drawings, and each of the accompanying drawings does not constitute a limitation on the embodiments of the present invention.
[0025] On the one hand, according to the present invention, a platinum-doped iron-aluminum alloy magnetostrictive material is provided, wherein the magnetostrictive material is Fe 0.80 Al 0.20 The alloy is the matrix and is obtained by doping Pt to replace Fe or Al.
[0026] The inventors have found that by doping Pt instead of Fe or Al, the grains can be controlled. <100> direction, thereby improving the magnetostrictive performance of the magnetostrictive material.
[0027] In the present invention, in the magnetostrictive material, the energy of the crystal plane (100) is lower than that of the crystal plane (110).
[0028] In the present invention, by doping Pt element, Fe 0.80 Al 0.20 The magnetostriction value of the alloy is increased from 29 ppm in the undoped state to 50~80 ppm.
[0029] In the present invention, the magnetostrictive material has the following expression: (Fe 0.80 Al 0.20 ) 100-x Pt x , x In atomic percentage, 0.2 ≤ x ≤1.0; preferably, 0.2≤ x ≤0.6; most preferably, x =0.4.
[0030] Furthermore, as the Pt content increases, the lattice parameter expands, the magnetic exchange coupling is enhanced, and the saturation magnetization increases. In addition, the relative intensity of the (100) peak increases. On the one hand, the volume proportion of the 90° flipped magnetic domain increases, and the magnetostrictive performance increases. On the other hand, the lattice constant increases, and the magnetostrictive constant also increases, so the magnetostrictive performance of the material shows an increasing trend. x When >0.4, the Pt element cannot further dissolve into the FeAl alloy, the lattice parameter decreases, the magnetic exchange coupling weakens, and thus the saturation magnetization decreases; in addition, the relative intensity of the (100) peak decreases, the lattice constant decreases, and the magnetostriction constant also decreases, thereby reducing the magnetostrictive properties of the material.
[0031] In the present invention, Pt is doped into Fe 0.80 Al 0.20 In the alloy matrix, the crystal growth direction was predicted by density functional theory calculation, and the Pt doped into Fe was preliminarily obtained. 0.80 Al 0.20 The effectiveness in the alloy matrix specifically includes the following steps: Step 1-1, constructing a block model; Step 1-2, construct a plate model based on the block model; Steps 1-3, based on the flat plate model, doping platinum atoms and obtaining surface energy; Steps 1-4, predict the crystal growth direction based on the surface energy.
[0032] According to a preferred embodiment, step 1-1 comprises: Step 1-1-1, select the crystal structure; Step 1-1-2, constructing a supercell according to the crystal structure; Step 1-1-3, perform full relaxation optimization on the supercell to obtain a bulk model.
[0033] In step 1-1-1, it is determined that the crystal structure of the iron-aluminum alloy is a body-centered cubic (BCC) structure.
[0034] In step 1-1-2, Fe was constructed using the VASP program. 43 Al 11 The A2 structure of the alloy, due to Fe 43 Al 11 The A2 structure of the alloy is a random disordered structure. The SQS method is used to construct a 3x3x3 BCC supercell, which is close to the Fe 0.80 Al 0.20 .
[0035] In step 1-1-3, set the wave function cutoff energy to 400-600 eV in the VASP program, for example, 400 eV; use the projected augmented wave (PAW) method, spin-polarized generalized gradient approximation (GGA), and Perdew-Burke-Ernzerhof (PBE) exchange-correlation function to fully relax the supercell, use a 3x3x3 Monkhorst-Pack k-point grid for Brillouin zone integration, and fully relax the atomic positions and lattice constants in the supercell until the energy and force differences are less than 10, respectively. -5 eV and 0.01 eV / Å.
[0036] In step 1-2, based on the block model, a flat plate model containing six atomic layers is created, which are perpendicular to the (100) crystal plane and the (110) crystal plane. The flat plate model simulates a periodic structure in a plane horizontal and perpendicular to the paper surface, that is, it is infinite in this plane; the flat plate model contains different surface combinations, excluding the flat plate of pure iron surface. Among them, the surface can be different crystal planes, that is, crystal plane (100) or crystal plane (110). Due to Fe 0.80 Al 0.20 The A2 (simple body-centered cubic) crystal structure is adopted, and the Fe and Al atoms are randomly occupied, so there will be a variety of surface combinations of atomic occupation.
[0037] In steps 1-3, before doping platinum atoms, set periodic boundary conditions in the x- and y-axis directions and set a vacuum space of at least 20 Å in the z-axis direction to avoid interaction between the slab and the periodic structure.
[0038] Furthermore, once the plate model is constructed, the periodic boundary conditions in the x- and y-axis directions can be determined.
[0039] In steps 1-3, only one Pt atom was doped on each surface of the Fe-Al plate, and the effect of Pt was observed.
[0040] In steps 1-3, the two middle atomic layers are fixed and only the atoms in the surface layer are allowed to relax.
[0041] In steps 1-3, the surface energy is obtained by: , where E slab is the total energy of the plate model, E bulk is the total energy of the block model, and S is the surface area of the plate model.
[0042] In steps 1-3, since there are multiple surface combinations, E S is the average value of all plate models.
[0043] In step 1-4, according to the difference in surface energy between the (100) crystal plane and the (110) crystal plane, , determine the crystal growth direction. A positive value means that during the crystal growth process, the (110) crystal plane has lower energy and is more stable than the (100) crystal plane; A negative value means that during the crystal growth process, the (100) crystal plane has lower energy and is more stable than the (110) crystal plane. At this time, the crystal growth direction is parallel to the easy magnetization axis, and the magnetostrictive performance is better.
[0044] In step 1-4, the inventors found that Pt doped into Fe 0.80 Al 0.20 In the alloy matrix, is a negative value, so Fe is modified by Pt 0.80 Al 0.20 The product obtained from the alloy matrix has an excellent magnetostriction value. Further, based on the above conclusions, a magnetostrictive material is obtained by smelting and homogenizing iron, aluminum and platinum. The inventor has conducted a large number of experimental studies and found that when iron, aluminum and platinum meet the requirements of (Fe 0.80 Al 0.20 ) 100-x Pt x When <100> The magnetostrictive material produced is much better than Fe 0.80 Al 0.20 The magnetostrictive properties of the alloy are effectively improved.
[0045] On the other hand, according to the present invention, there is provided a method for preparing the magnetostrictive material according to the first aspect, the method comprising: Step 1, smelting raw materials to obtain magnetostrictive ingots; Step 2: homogenizing the magnetostrictive ingot to obtain the magnetostrictive material.
[0046] In step 1, the composition of the raw material is obtained by density functional theory calculation, that is, the density functional theory calculation is used to preliminarily obtain the Pt doped Fe0.80 Al 0.20 effectiveness in alloy matrix.
[0047] In step 1, the raw materials include iron, aluminum and platinum.
[0048] Furthermore, the raw material satisfies the following expression: (Fe 0.80 Al 0.20 ) 100-x Pt x , x In atomic percentage, 0.2 ≤ x ≤1.0; preferably, 0.2≤ x ≤0.6; most preferably, x =0.4.
[0049] In step 1, the purity of iron is not less than 99.9%, the purity of aluminum is not less than 99.95%, and the purity of platinum is not less than 99.95%. In one embodiment, the purity of iron is 99.95%, the purity of aluminum is not less than 99.95%, and the purity of platinum is not less than 99.95%. In step 1, the smelting is carried out in an inert gas such as argon to prevent the molten metal from reacting with oxygen, nitrogen, etc. in the air.
[0050] In step 1, the smelting pressure is 3×10 4 ~4×10 4 Pa, for example 3.5×10 4 Pa. Appropriate pressure during smelting helps control the melt flow and the escape of metal vapor during the smelting process, and also helps maintain the temperature uniformity in the smelting furnace.
[0051] In step 1, before filling the melting furnace with inert gas, the vacuum is evacuated to 4 × 10 -3 ~6×10 -3 Pa, for example, vacuum to 5×10 -3 Pa, and then filled with inert gas. Under high vacuum conditions, oxygen, nitrogen and other gas impurities in the smelting furnace can be effectively removed. These impurities may react with the molten metal and affect the purity and performance of the product.
[0052] In step 1, the smelting temperature is 1600-1800°C.
[0053] Furthermore, the above smelting temperature is sufficient to melt iron, aluminum and platinum metals, and is conducive to the re-nucleation and growth of grains, thereby obtaining a finer grain structure, which is beneficial to improving the performance of the magnetostrictive material; in addition, at high temperatures, certain impurity elements are more easily volatilized, thereby further purifying the magnetostrictive material.
[0054] In step 1, the melting times are preferably 3 to 5 times, for example, 4 times. Repeated melting helps to promote the uniform distribution of magnetostrictive material components, reduce microsegregation, and improve the uniformity of magnetostrictive materials. The 4 melting temperatures can be 1600 to 1800°C to promote element convection and make the sample homogenized, for example, 1600°C, 1650°C, 1700°C and 1800°C respectively.
[0055] In step 1, the smelting is preferably achieved by arc melting technology, more preferably in a non-consumable vacuum arc melting furnace. The non-consumable vacuum arc melting furnace can melt metals in an inert gas environment of appropriate pressure, reducing the incorporation of oxidation and other impurities, thereby producing materials with very high purity; and it is convenient to perform multiple melting and solidification, which helps to homogenize the chemical composition of the material and reduce segregation.
[0056] In step 2, the homogenization treatment includes: high temperature treatment in an inert gas, followed by rapid cooling.
[0057] Furthermore, the inert gas is preferably argon.
[0058] Furthermore, the high temperature is 800-1200° C., preferably 900-1100° C., for example 1000° C.; the high temperature insulation time is 18-36 h, preferably 20-24 h, for example 24 h.
[0059] Among them, the high temperature treatment is for atomic diffusion and the reduction of defects such as vacancies and dislocations. Such a long time is to fully ensure the reduction of defects, facilitate the movement and flipping of magnetic domains, and increase magnetostrictive properties. The above temperature and time ranges are more appropriate.
[0060] In step 2, the rapid cooling is preferably quenching in water.
[0061] Among them, rapid cooling can quickly reduce the temperature of the alloy, prevent grain growth, maintain a fine and uniform grain structure, avoid the formation of the second phase, and maintain the phase structure of the magnetostrictive material. Water quenching uses water as a cooling medium, which is low in cost and easy to obtain, making water quenching an economical and practical cooling method.
[0062] The present invention is further described below through specific examples, but these examples are merely exemplary and do not constitute any limitation to the scope of protection of the present invention.
[0063] Example 1
[0064] Prove that Pt doping into Fe 0.80 Al 0.20 Effectiveness in alloy matrix The crystal structure of the Fe-Al alloy was determined to be a body-centered cubic (BCC) structure, and the Fe 43 Al 11 The A2 structure of the alloy is constructed by the SQS method to construct a 3x3x3 BCC supercell, which is close to Fe 0.80 Al 0.20 The wave function cutoff energy was set to 400 eV in the VASP program. The projected augmented wave (PAW) method, spin-polarized generalized gradient approximation (GGA), and Perdew-Burke-Ernzerhof (PBE) exchange-correlation function were used to fully relax the supercell. A 3x3x3 Monkhorst-Pack k-point grid was used for Brillouin zone integration. The atomic positions and lattice constants in the supercell were fully relaxed until the energy and force differences were less than 10, respectively. -5 eV and 0.01 eV / Å, and a bulk model is obtained.
[0065] Based on the bulk model, a flat plate model containing six atomic layers was created, which were perpendicular to the (100) crystal plane and the (110) crystal plane respectively; the flat plate model contained different surface combinations, with Fe and Al atoms randomly occupying positions, and did not include the flat plate on the surface of pure iron; after the flat plate model was built, the periodic boundary conditions in the x and y axis directions were determined, and the vacuum space in the z axis direction was set to 20Å. After that, the two middle atomic layers were fixed, and only the atoms in the surface layer were allowed to relax; only one Pt atom was doped on each surface of the Fe-Al plate to observe the effect of Pt.
[0066] Figure 1 (c) shows the schematic diagram of the six-atom-layer slab model after the (100) crystal plane is doped with Pt. Figure 1 (d) shows the schematic diagram of the six-atom-layer slab model after the (110) crystal plane is doped with Pt. Table 1 shows the total energy of the six planes of the Pt-doped Fe-Al-Pt structure, where the surface areas of the (100) crystal plane and the (110) crystal plane are 75.184 Å, respectively. 2 and 105.377 Å 2 .
[0067]
[0068] It is obvious that the energy of the (100) and (110) crystal planes is and , then the energy difference is This indicates that the energy relationship between the (100) and (110) planes has reversed, which means that during the crystal growth process, the (100) and (110) planes have lower energy and are more stable. Ultimately, the crystal growth direction is parallel to the easy magnetization axis, which preliminarily determines that Pt doping into Fe 0.80 Al 0.20 effectiveness in alloy matrix.
[0069] Example 2 Preparation of magnetostrictive materials: Press (Fe 0.80 Al 0.20 ) 99.6 Pt 0.4 Take 99.95% pure iron, 99.99% pure aluminum and 99.99% pure platinum in atomic percentage, put the weighed iron, aluminum and platinum into a copper crucible in a non-consumable vacuum arc melting furnace, close the furnace door and evacuate to 5.0×10 -3 Pa, and then filled with high-purity argon gas to 3.5×10 4 Pa, smelted at 1600-1800°C, smelted 4 times in total (the 4 times of temperature were 1600°C, 1650°C, 1700°C and 1800°C respectively), to obtain magnetostrictive ingots; The magnetostrictive ingot was cut into 1 mm thick crescent pieces along the cross-section line, and then filled with high-purity argon gas after vacuum sealing. The tube was kept at 1000 ° C for 24 h, and then quenched in water to obtain a composition of (Fe 0.80 Al 0.20 ) 99.6 Pt 0.4 magnetostrictive material.
[0070] After testing, the magnetostriction value of the prepared magnetostrictive material is 80 ppm, and the relative intensity of the (100) peak is 30.902.
[0071] Example 3 Preparation of magnetostrictive materials Press (Fe 0.80 Al 0.20 ) 99.8 Pt 0.2 Take 99.95% pure iron, 99.99% pure aluminum and 99.99% pure platinum in atomic percentage, put the weighed iron, aluminum and platinum into a copper crucible in a non-consumable vacuum arc melting furnace, close the furnace door and evacuate to 5.0×10 -3 Pa, and then filled with high-purity argon gas to 3.5×10 4Pa, smelted at 1600-1800°C, smelted 4 times in total (the 4 times of temperature were 1600°C, 1650°C, 1700°C and 1800°C respectively), to obtain magnetostrictive ingots; The magnetostrictive ingot was cut into 1 mm thick crescent pieces along the cross-section line, and then filled with high-purity argon gas after vacuum sealing. The tube was kept at 1000 ° C for 24 h, and then quenched in water to obtain a composition of (Fe 0.80 Al 0.20 ) 99.8 Pt 0.2 The magnetostrictive material has a magnetostrictive value of 52 ppm.
[0072] Example 4 Preparation of magnetostrictive materials Press (Fe 0.80 Al 0.20 ) 99.4 Pt 0.6 Take 99.95% pure iron, 99.99% pure aluminum and 99.99% pure platinum in atomic percentage, put the weighed iron, aluminum and platinum into a copper crucible in a non-consumable vacuum arc melting furnace, close the furnace door and evacuate to 5.0×10 -3 Pa, and then filled with high-purity argon gas to 3.5×10 4 Pa, smelting at 1600-1800°C (the temperatures of the four times are 1600°C, 1650°C, 1700°C and 1800°C respectively), smelting a total of 4 times, to obtain a magnetostrictive ingot; The magnetostrictive ingot was cut into 1 mm thick crescent pieces along the cross-section line, and then filled with high-purity argon gas after vacuum sealing. The tube was kept at 1000 ° C for 24 h, and then quenched in water to obtain a composition of (Fe 0.80 Al 0.20 ) 99.4 Pt 0.6 The magnetostrictive material has a magnetostrictive value of 54 ppm.
[0073] Comparative Example 1 (1) The crystal structure of the Fe-Al alloy was determined to be a body-centered cubic (BCC) structure. The VASP program was used to construct the Fe 43 Al 11 The A2 structure of the alloy is constructed by the SQS method to construct a 3x3x3 BCC supercell, which is close to Fe 0.80 Al 0.20The wave function cutoff energy was set to 400 eV in the VASP program. The projected augmented wave (PAW) method, spin-polarized generalized gradient approximation (GGA), and Perdew-Burke-Ernzerhof (PBE) exchange-correlation function were used to fully relax the supercell. A 3x3x3 Monkhorst-Pack k-point grid was used for Brillouin zone integration. The atomic positions and lattice constants in the supercell were fully relaxed until the energy and force differences were less than 10, respectively. -5 eV and 0.01 eV / Å, and a bulk model is obtained.
[0074] Based on the block model, a flat plate model containing six atomic layers is created, which are perpendicular to the (100) crystal plane and the (110) crystal plane respectively; the flat plate model contains different surface combinations, with Fe and Al atoms randomly occupying positions, and does not include a flat plate on the surface of pure iron; after the flat plate model is constructed, the periodic boundary conditions in the x and y axis directions can be determined, and the z axis direction can be set to a vacuum space of 20Å.
[0075] Figure 1 (a) shows a schematic diagram of the six-atom-layer slab model of the (100) crystal plane. Figure 1 (b) shows a schematic diagram of the six-atom-layer slab model of the (110) crystal plane. Table 2 shows the total energy of the six planes of the Fe-Al structure, where the surface areas of the (100) and (110) crystal planes are 75.184 Å, respectively. 2 and 105.377 Å 2 .
[0076] Table 2:
[0077] It is obvious that the energy of the (100) and (110) crystal planes is , , then the energy difference is This indicates that the (110) and (100) crystal planes have lower energy and are more stable.
[0078] (2) According to Fe 0.80 Al 0.20 The atomic percentage of (x=0) is 99.95% pure iron and 99.99% pure aluminum. The weighed iron and aluminum are placed in a copper crucible in a non-consumable vacuum arc melting furnace. The furnace door is closed and the vacuum is pumped to 5.0×10 -3 Pa, and then filled with high-purity argon gas to 3.5×10 4 Pa, smelting at 1600-1800°C (the temperatures of the four times are 1600°C, 1650°C, 1700°C and 1800°C respectively), smelting a total of 4 times, to obtain a magnetostrictive ingot; The magnetostrictive ingot was cut into 1 mm thick crescent pieces along the cross-section line, and then filled with high-purity argon gas after vacuum sealing. The tube was kept at 1000 ° C for 24 h, and then quenched in water to obtain a composition of Fe 0.80 Al 0.20 magnetostrictive material.
[0079] After testing, the magnetostrictive value of the prepared magnetostrictive material is 29 ppm, and the relative intensity of the (100) peak is 0.228. It can be seen that the magnetostrictive performance of the magnetostrictive material prepared in Example 2 is improved by 176% compared with that of Comparative Example 1.
[0080] Figure 2 The XRD characterization of the crescent flakes obtained by melting in Examples 2-4 and Comparative Example 1 is shown. It can be seen that after Pt is added, the intensity of the (200) peak changes significantly relative to the intensity of the (110) peak.
[0081] Figure 3 A comparison of the normalized relative intensity of the (100) peak of the magnetostrictive materials prepared in Examples 2-4 and Comparative Example 1 (the ratio of the (200) peak intensity to the (110) peak intensity) is shown. It can be seen that the magnetostrictive material doped with 0.4% Pt in Example 2 significantly enhances the (100) peak orientation, which is consistent with the VASP theoretical prediction.
[0082] Figure 4 The strain test diagrams of the crescent pieces obtained by melting in Examples 2-4 and Comparative Example 1 are shown. It can be seen that after Pt addition, the magnetostrictive performance of the magnetostrictive material is greatly improved, especially when x=0.4, the magnetostrictive performance is improved the most.
[0083] The magnetostrictive materials prepared in Examples 2-4 and Comparative Example 1 were respectively ground with sandpaper and then polished with a 0.04 μm silica suspension for 30 minutes, and the magnetic domains were observed under a magnetic force microscope. Figure 5 (a) shows the magnetic domain diagram of the magnetostrictive material prepared in Comparative Example 1; Figure 5 (b) shows the magnetic domain diagram of the magnetostrictive material prepared in Example 3; Figure 5 (c) shows the magnetic domain diagram of the magnetostrictive material prepared in Example 2; Figure 5 (d) shows the magnetic domain diagram of the magnetostrictive material prepared in Example 4; it can be seen that after the magnetic domain is doped with Pt, the orientation of the labyrinth magnetic domain is enhanced, and a strip-shaped magnetic domain is obtained when x=0.4. Based on the above examples, the magnetostrictive material prepared in Example 2 has the best performance.
[0084] After testing, the currently commercialized Terfenol-D giant magnetostrictive material has an excited saturation magnetization field of 3 kOe, a yield strength of 30 MPa, and an elongation of less than 1%, while the excited saturation magnetization field of the magnetostrictive material obtained in Example 2 is 1 kOe, the yield strength is 500 MPa, and the elongation is greater than 10%. It can be seen that the excited saturation magnetization field of the magnetostrictive material obtained in Example 2 is much smaller, and the brittleness is smaller than that of the magnetostrictive material, and the plasticity is better.
[0085] The present invention is described in detail above in combination with preferred embodiments and exemplary examples. However, it should be noted that these specific embodiments are only illustrative explanations of the present invention and do not constitute any limitation on the protection scope of the present invention. Without exceeding the spirit and protection scope of the present invention, various improvements, equivalent substitutions or modifications may be made to the technical content of the present invention and its embodiments, which all fall within the protection scope of the present invention. The protection scope of the present invention shall be subject to the attached claims.
Claims
1. A platinum-doped iron-aluminum alloy magnetostrictive material, characterized in that: The magnetostrictive material is Fe 0.80 Al 0.20 The alloy is the matrix and is obtained by doping Pt to replace Fe or Al.
2. The magnetostrictive material according to claim 1, characterized in that Preferably, by doping Pt instead of Fe or Al, the grains are controlled <100> direction to improve the magnetostrictive performance of the magnetostrictive material.
3. The magnetostrictive material according to claim 1, characterized in that In the magnetostrictive material, the energy of the crystal plane (100) is lower than that of the crystal plane (110).
4. The magnetostrictive material according to claim 1, characterized in that The magnetostriction value of the magnetostrictive material is 50-80 ppm.
5. The magnetostrictive material according to claim 1, characterized in that The magnetostrictive material has the following expression: (Fe 0.80 Al 0.20 ) 100-x Pt x , x In atomic percentage, 0.2 ≤ x ≤1.
0.
6. A method for preparing the magnetostrictive material according to any one of claims 1 to 5, characterized in that: The method comprises: Step 1, smelting raw materials to obtain magnetostrictive ingots; Step 2: homogenizing the magnetostrictive ingot to obtain the magnetostrictive material.
7. The method according to claim 6, characterized in that In step 1, the raw materials include iron, aluminum and platinum.
8. The method according to claim 7, characterized in that The purity of the iron is not less than 99.9%.
9. The method according to claim 7, characterized in that: The purity of the aluminum is not less than 99.95%.
10. The method according to claim 7, characterized in that The purity of the platinum is not less than 99.95%.